PS2-16: Racial Disparities in Biobank Participation among Women in Southern California - Koebnick, Corinna (Clin Med Res, 2014)
BACKGROUND/AIMS: The aim of this study is to identify predictors of participation in women of different racial groups to optimize future recruitment efforts. METHODS: We randomly selected and assessed predictors of participation on Kaiser Permanente Southern California adult female members (n = 107,378) between November 2012 and June 2013. Women were asked to provide a saliva sample for a research biobank. Potential predictors of participation were age, long-term membership (= 5 years), no significant gaps in health care coverage (<3 month in last 3 years), physical examination within the last 3 years and neighborhood education and income. RESULTS: The overall participation among women was 6.8%. Restricting recruitment to women with = 5 years of membership, no major gaps in health care coverage, and at least one physical examination within the last 3 years improved participation in Whites (from 7.1% to 14.3) and Hispanics (from 2.5% to 5.0%) but only modestly in Blacks (from 2.0% to 3.6%). In logistic regression models predicting participation, the strongest predictors in Whites and Hispanics were having a physical examination (OR 1.25, 95%-CI 1.17–1.33 in Whites and 1.45, 1.28–1.65 in Hispanics) and long-term membership (OR 1.19, 95%-CI 1.12–1.27 in Whites and 1.32, 1.16–1.50 in Hispanics). None of the restrictions significantly predicted participation in Blacks (p for interaction with race <0.001). CONCLUSIONS: Applying restrictions based on regular physical examinations and longer membership may potentially increase participation of non-Hispanic White and Hispanic women in a research biorepository.